Enhancing Energy Efficiency in Mediterranean Coastal Buildings Through PCM Integration - Chawki Lahoud; Antoine Chahwan; Jihad Rishmany; Chafic Yehia; Michel Daaboul (Buildings)
In this paper, the impact of phase change material (PCM) integration into building envelopes is evaluated, considering a coastal mediterranean climate. PCM integration represents an innovative technology to lower construction’s heating and cooling loads. A case study was conducted on PCM integration into a Lebanese structure’s envelope where the thermal performance and energy effectiveness were assessed. A significant reduction was observed for both cooling and heating loads. Simulations revealed that the optimal PCMs were those whose melting temperatures were between 21 °C and 24 °C under the Mediterranean weather conditions, showing the importance of selecting the appropriate PCM to enhance energy savings. The annual energy savings calculated were between 11% and 13.4%. The study also emphasized the impact of the specified heating and cooling temperatures within the comfort range on the effectiveness of PCM integration. The results show that optimal PCM selection is a function of the weather conditions and indoor temperature settings.